ANALISIS NILAI-NILAI PENDIDIKAN DALAM NOVEL PEREMPUAN YANG MENDAHULUI ZAMAN KARYA KHAIRUL JASMI SERTA RELEVANSINYA TERHADAP PENDIDIKAN DASAR - Gina Hayati, Nurul; Hasanah, Offi; Adrias; Azmi Alwi, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education at the elementary school level is one of the important aspects in shaping students’ personalities holistically. Literary works, especially biographical novels, can be utilized as contextual learning resources because they contain various life values relevant to education. This study aims to analyze the educational values contained in the novel Perempuan yang Mendahului Zaman by Khairul Jasmi and examine their relevance to elementary education. The research employed a qualitative descriptive method with a content analysis approach. The data source of this study was the novel Perempuan yang Mendahului Zaman, which was systematically analyzed through coding, categorization, and data interpretation processes. Data analysis techniques were conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through persistent observation and theory triangulation. The analysis of educational values in this study referred to the concept of character education proposed by Thomas Lickona, which includes the aspects of moral knowing, moral feeling, and moral action. The results showed that the novel contains religious values, independence, responsibility, perseverance, and a spirit of struggle in education. These values have strong relevance to the goals of elementary education in shaping students’ character. The conclusion of this study indicates that biographical novels can be utilized as value- and character-based learning resources in elementary education.